2008
DOI: 10.2478/10004-1254-59-2008-1907
|View full text |Cite
|
Sign up to set email alerts
|

Asbestosis and Catalase Genetic Polymorphism

Abstract: Catalase (CAT) is part of the enzymatic defense system against reactive oxygen species (ROS), known to be involved in the pathogenesis of asbestosis. This study investigates whether CAT -262 C>T genetic polymorphism influences the risk of asbestosis in workers occupationally exposed to asbestos. The nested case-control study included 262 cases with asbestosis and 265 controls with no asbestosrelated disease. Data on cumulative asbestos exposure and smoking were available. A real-time PCR assay was introduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…An elevated risk of asbestosis was also observed for the ECSOD 213Arg/Gly genotype, CAT −262 TT genotype and iNOS LL genotype, but the results were not significant or borderline significant [68]. In this paper, we additionally present the interactions between different genotypes, genotypes and smoking, and between genotypes and cumulative asbestos exposure.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated risk of asbestosis was also observed for the ECSOD 213Arg/Gly genotype, CAT −262 TT genotype and iNOS LL genotype, but the results were not significant or borderline significant [68]. In this paper, we additionally present the interactions between different genotypes, genotypes and smoking, and between genotypes and cumulative asbestos exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that patients with C262C genotype have lower CAT activity, which can cause accumulation of free radicals and oxidative stress. The association between the CAT C262T SNP was found to have an effect on the predisposition to male infertility [39], Shigella flexneri- related infection [40], asbestosis [41], vitiligo [42], and cancer although it remains highly contradictory and inconclusive [43]. …”
Section: Discussionmentioning
confidence: 99%
“… 14 Our previous study investigating the association of this polymorphism with asbestosis found a slight increase in the risk of the TT genotype. 16 Superoxide dismutases (SOD) convert superoxide into H 2 O 2 and O 2 . SOD2 is found in mitochondria, where the amount of ROS is very high.…”
Section: Introductionmentioning
confidence: 99%
“… 27 We have previously described the association between SOD2 Ala/Ala genotype and asbestosis 28 as well as association between CAT -262 TT genotype and asbestosis. 16 Landi et al . reported on the association between SOD2 and the risk of MM 25 , but according to our knowledge and available literature, the impact of NQO1 , CAT and hOGG1 polymorphisms on the risk of developing MM has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%